SOSIALISASI BAHAYA MEMBUANG SAMPAH SEMBARANGAN DAN MENENTUKAN LOKASI TPA DI DUSUN DELES DESA JAGONAYAN KECAMATAN NGABLAK - Arif Fajar Wibisono (UII, 2014)
Dusun Deles, Jogonayan village, District Ngablak, Magelang, Central Java consistingof 3 RW and 12 RT. Mostly livelihood society is a farmer. Besides his profession as afarmer, society Also worked as traders, civil servants, workers, etc. People in the DusunDeles is people who have a high desire to advance Dusun Deles, this can be proved onthe willingness of citizens to cooperate and worked -together for development in DusunDeles. On the physical development and infrastructure which was a highlight for thecitizens Deles is the concept of waste disposal sites. The concept of waste disposal sitesas well as solutions to problems Deles village hygiene and raise the awareness of citizensto dispose of waste in place. The need for infrastructure in Dusun Deles is desperatelyneeded, not just for the media spotlight that this village will progress its developmentbut also as a useful tool to promote and support the activities of citizens.